2020
DOI: 10.3390/microorganisms8101484
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in Spatial Turnover of Bacterioplankton Along an Ecological Gradient in the East China Sea: Biogeographic Patterns, Processes and Drivers

Abstract: Seasonal succession in bacterioplankton is a common process in marine waters. However, seasonality in their spatial turnover is largely unknown. Here, we investigated spatial turnover of surface bacterioplankton along a nearshore-to-offshore gradient in the East China Sea across four seasons. Although seasonality overwhelmed spatial variability of bacterioplankton composition, we found significant spatial turnover of bacterioplankton along the gradient as well as overall seasonal consistency in biogeographic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…Environmental selection, primarily temperature, was stronger than dispersal limitation in accounting for variation among bacterial assemblages (17% vs 11%); this finding agrees with several prior studies of marine bacterioplankton ( Hanson et al, 2012 ; Hu et al, 2020 ; Milici et al, 2016 ; Sunagawa et al, 2015 ). Relatively weaker spatial patterning in bacteria supports the “size-dispersal” hypothesis, i.e ., that smaller organisms have higher dispersal rates, especially when dispersal is primarily passive ( De Bie et al, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Environmental selection, primarily temperature, was stronger than dispersal limitation in accounting for variation among bacterial assemblages (17% vs 11%); this finding agrees with several prior studies of marine bacterioplankton ( Hanson et al, 2012 ; Hu et al, 2020 ; Milici et al, 2016 ; Sunagawa et al, 2015 ). Relatively weaker spatial patterning in bacteria supports the “size-dispersal” hypothesis, i.e ., that smaller organisms have higher dispersal rates, especially when dispersal is primarily passive ( De Bie et al, 2012 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in general accord with Mo et al (2018) who likewise found stochastic factors to be primary in bacterioplankton community assembly in open-ocean habitat, albeit at a somewhat lower level of dominance (57%). However, several other studies found deterministic factors to be more important relative to neutral processes in similar scenarios ( Allen et al, 2020 ; Hu et al, 2020 ; Vergin et al, 2017 ; Wu et al, 2018 ). Although spatial factors comprise a portion of the neutral process ( Hubbell, 2001 ), the strength of the NCM in our study does not contradict the relatively small spatial effect revealed by variation partitioning.…”
Section: Discussionmentioning
confidence: 87%
“…Bray–Curtis similarity is one of the most commonly used similarity quantification methods when it comes to ecological abundance data collected at different sampling locations (Legendre and Legendre, 2012; Ricotta and Podani, 2017). Principal coordinates analysis explores similarities or dissimilarities, such as Bray–Cutis similarity, and takes species identity into account, which is a better method of analysing bacterial community structure data for VPA (Mohammadi and Prasanna, 2003; Legendre and Legendre, 2012; Hamdan et al ., 2013; Nagaraj et al ., 2017; Hu et al ., 2020). To avoid collinearity in the statistical calculation, principal coordinates axes with a cumulative 73.9% variation based on Bray–Curtis similarity were used to summarize the bacterial community structure (relative abundance data) for VPA.…”
Section: Methodsmentioning
confidence: 99%
“…Mariculture represents one of the fastest growing industrial sectors in the world, but from the perspective of nutrient load and structural damage, the impact of mariculture on the environment is considerable. Microorganisms form the basis of marine food webs and are crucial for biogeochemical cycles [15] , [18] , [51] . Yet, there are many unknowns on how microorganisms respond to environmental interferences from mariculture activities [2] , [27] , [38] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms are regarded as one of the major food web components of coastal ecosystems controlling biogeochemical cycles in coastal environments to a large extent [51] . Thus, exploring the spatial pattern of microbial communities related to environmental factors is crucial to reveal the role of microbial communities for the entire coastal food web and biogeochemical cycles [15] , [18] , [40] .…”
Section: Introductionmentioning
confidence: 99%